2022
DOI: 10.1111/ced.15133
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of time to definitive surgery and survival in Merkel cell carcinoma: analysis of the US National Cancer Database

Abstract: Background. Merkel cell carcinoma (MCC) is an aggressive cancer, and it has been suggested that earlier treatment would allow for better patient outcomes. However, the causes of delays in the initiation of treatment and the effects of delayed treatment on survival of patients have not fully been explored, and the effects of treatment delays for MCC are not yet fully understood. Aim. To determine the effect of time to treatment initiation (TTI) on mortality in MCC and to determine the predictors of TTI itself. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This is consistent with some prior studies using the NCDB. [9][10][11] From the splines (Figure S1), IT appears that time to surgery may play more of a role than time from surgery to radiation. However, the present study had a positive finding when looking at time from diagnosis to radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with some prior studies using the NCDB. [9][10][11] From the splines (Figure S1), IT appears that time to surgery may play more of a role than time from surgery to radiation. However, the present study had a positive finding when looking at time from diagnosis to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…8 More recent studies using the National Cancer Database have found no link between survival and time from surgery to radiation treatment, 9,10 or between survival and time from diagnosis to surgery. 11 Anecdotally, we have noted that depending on clinical course, treatment choices, and access to care, time to radiation for individual patients may vary greatly. We sought to use a comprehensive, national cohort to investigate factors influencing time to initiation of RT and its impact on survival among MCC patients who received surgical excision and adjuvant radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The NCDB is a nationwide clinical surveillance resource data set that includes approximately 70% of all newly diagnosed malignant neoplasms in the US from more than 1500 cancer programs . Data from the NCDB have been used in multiple previous studies of cutaneous oncologic outcomes . This study was deemed not to be human participant research and was therefore exempt from institutional review board review by the New York University Langone Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…27,28 Data from the NCDB have been used in multiple previous studies of cutaneous oncologic outcomes. 15,[29][30][31][32] This study was deemed not to be human participant research and was therefore exempt from institutional review board review by the New York University Langone Institutional Review Board. Informed consent was not obtained because this was not human participant research.…”
Section: Data Sourcementioning
confidence: 99%
“… 6 , 7 However, multivariate analysis of data from SEER 17 (1988–2012) and NCDB (2004–2016) failed to establish an association between race and survival. 4 , 9 Studies to resolve these inconsistencies and better understand MCC disparities are needed.…”
mentioning
confidence: 99%